Bentuk Penyajian Tari Rahim Sungai Musi di Sungai Ogan Kampung 15 Ulu Kota Palembang - Tamaran Yustitia Balqis; Dessy Wardiah; Nugroho Notosutanto Arhon Dhony (SENDRATASIK UNP, 2023)
The Rahim Sungai Musi Dance is a dance that tells of diversity and ethnic diversity along the banks of the Musi River involving 43 women of various ages, teenagers to adults. The research problem is how the form of the presentation of the Rahim Sungai Musi Dance in the Ogan River, village 15 Ulu, Palembang City. The aim of this research is to find out and describe the form of presentation of the Musi River Rahim Dance in the Ogan River, village 15 Ulu, Palembang City. This research uses qualitative methods with data collection techniques in the form of observation, interviews, documentation, and literature study. The form of presentation of the Rahim Sungai Musi Dance, namely the overall form presented on stage, consists of conceptual aspects and dance performances including dance moves, dance space, dance music, dance titles, themes, dance types, presentation modes, dancers, fashion, make-up, and styling, Light, property. From the results of the research and analysis it was concluded that the Rahim Sungai Musi Dance is a dance work that developed in the post-traditional era with the themes of historical, ecological and cultural issues that describe the activities of riverside communities such as fishing, washing, boats as a means of transportation, and the existence of floating markets in ancient time.